(untitled) (Scientific journal of the Fergana State University, 2024)
This article refers to proverbs that are examples of folklore. In the process of revealing the meaning and content of the proverbs in the works, they also express some of the characters of the heroes of the work. In this article, we will get acquainted with proverbs from works of ancient and modern times. At the same time, folk art not only forms concepts about the characters in the works, but also shows their negative and positive images. Also presented are “Devonu Lugotit Turk”, “Kutadgu-bilig”, “Zarbulmasal” and a number of other works written in Persian, which are rare examples of Turkish literature. In addition, several other stories are mentioned. The main purpose of writing an article is to find articles in works and reveal their meaning.